Distribution of Japanese Eel Anguilla japonica Revealed by Environmental DNA - Kasai, Akihide; Yamazaki, Aya; Ahn, Hyojin; Yamanaka, Hiroki; Kameyama, Satoshi; Masuda, Reiji; Azuma, Nobuyuki; Kimura, Shingo; Karaki, Tatsuro; Kurokawa, Yuko; Yamashita, Yoh (Frontiers in Ecology and Evolution, 2021)
The abundance of Japanese eel Anguilla japonica has rapidly decreased in recent decades. Following a re-evaluation of the possibility of extinction, the Japanese Ministry of the Environment and the International Union for Conservation of Nature listed the Japanese eel as an endangered species in 2013 and 2014, respectively. However, their abundance and precise distribution have never been clarified owing to their nocturnality and difficulty in their capture. In this study, the distribution of Japanese eels was investigated by monitoring for environmental DNA (eDNA), a non-invasive and efficient detection method. A total of 365 water samples were collected from 265 rivers located throughout Japan. High concentrations of eDNA of Japanese eels were detected in rivers on the Pacific side, but were low in the Sea of Japan side. In particular, very little eDNA amplification was confirmed from Hokkaido and the north of the Sea of Japan. The eDNA distribution in Japanese rivers coincides with the transport of the larvae in the ocean, as estimated by numerical simulations. Generalized linear mixed models were developed to explain the distribution of eDNA concentrations. The total nitrogen concentration emerged as an important factor in the best model. These results indicate that the distribution of Japanese eel is mostly determined by the maritime larval transport, and their survival and growth depend on the abundance of food in the river. The findings of the present study are useful for the management of populations and in the conservation of Japanese eels.